Factors Encouraging Passengers to Prefer Rail Transportation in Iran Based On Law and Rights of Passengers - Razmfarsa, Ashkan; Amidi, Arian; Darvishmoghaddam, Ehsan; Khademi, Tayebeh (Jurnal Cita Hukum, 2022)
Platforms are critical components of every rail travel. At the train station, passengers can take benefit of a variety of platform-based amenities whose satisfaction is prioritized. Rail services play a critical role in carrying people and products from point of origin to point of destination. People's mobility has accelerated in recent years, with the ultimate goal of earning a living. Numerous forms of transportation are available to promote accessible modes of transportation to people in diverse parts of the world, including road, rail, air, and sea. Rail transport has developed into one of the most important modes of transport in recent decades in Iran, which is experiencing an increase in demand for rail services. The objective of this research is to identify and rank the elements that influence people's willingness to travel by train. The statistical population is comprised of all passengers who travel by rail on a daily basis, which amounts to approximately 75,000 persons. The statistical sample size was determined using the Morgan table, which yielded 382 passengers. Four factors can be examined when determining whether to increase people's desires: economy, station conditions, journey time, and train conditions, with economy and train conditions being the most essential. The study's conclusions can assist commercial and public railway businesses in providing the required infrastructure and circumstances to boost passenger appeal.Keywords: Economics; Passenger’s Law; Rail Transportation; Station circumstances Faktor Pendorong Penumpang Untuk Memilih Transportasi Kereta Api di Iran Berdasarkan Hukum dan Hak Penumpang Abstrak Platform adalah komponen penting dari setiap perjalanan kereta api. Di stasiun kereta, penumpang dapat memanfaatkan berbagai fasilitas berbasis peron yang mengutamakan kepuasan. Layanan kereta api memainkan peran penting dalam membawa orang dan produk dari titik asal ke titik tujuan. Mobilitas orang telah meningkat dalam beberapa tahun terakhir, dengan tujuan akhir mencari nafkah. Berbagai bentuk transportasi tersedia untuk mempromosikan moda transportasi yang dapat diakses oleh orang-orang di berbagai belahan dunia, termasuk jalan raya, kereta api, udara, dan laut. Transportasi kereta api telah berkembang menjadi salah satu moda transportasi terpenting dalam beberapa dekade terakhir di Iran, yang mengalami peningkatan permintaan akan layanan kereta api. Tujuan dari penelitian ini adalah untuk mengidentifikasi dan mengurutkan elemen-elemen yang mempengaruhi keinginan masyarakat untuk bepergian dengan kereta api. Populasi statistik terdiri dari semua penumpang yang melakukan perjalanan dengan kereta api setiap hari, yang berjumlah sekitar 75.000 orang. Ukuran sampel statistik ditentukan dengan menggunakan tabel Morgan, yang menghasilkan 382 penumpang. Empat faktor dapat diperiksa ketika menentukan apakah akan meningkatkan keinginan masyarakat: ekonomi, kondisi stasiun, waktu perjalanan, dan kondisi kereta api, dengan ekonomi dan kondisi kereta menjadi yang paling penting. Kesimpulan studi dapat membantu bisnis perkeretaapian komersial dan umum dalam menyediakan infrastruktur dan keadaan yang diperlukan guna meningkatkan daya tarik penumpang.Kata Kunci: Ekonomi; Hukum Penumpang; Transportasi Kereta Api; Keadaan stasiun Факторы, побуждающие пассажиров предпочитать железнодорожные перевозки в Иране на основании закона и прав пассажиров Аннотация Платформы являются важными компонентами любого железнодорожного путешествия. На вокзале пассажиры могут воспользоваться различными удобствами на платформе, удовлетворение которых является приоритетом. Железнодорожные услуги играют решающую роль в перевозке людей и товаров из пункта отправления в пункт назначения. Мобильность людей ускорилась в последние годы с конечной целью зарабатывать на жизнь. Существуют различные виды транспорта для продвижения доступных видов перевозок для людей в разных частях мира, включая автомобильный, железнодорожный, воздушный и морской транспорт. За последние десятилетия железнодорожный транспорт превратился в один из важнейших видов транспорта в Иране, где наблюдается рост спроса на железнодорожные услуги. Целью данного исследования является выявление и ранжирование элементов, влияющих на готовность людей путешествовать на поезде. Статистическая совокупность состоит из всех пассажиров, которые ежедневно путешествуют по железной дороге, что составляет примерно 75.000 человек. Размер статистической выборки определялся с помощью таблицы Моргана, которая составила 382 пассажира. При определении того, следует ли увеличивать желания людей, можно изучить четыре фактора: экономика, условия станции, время в пути и условия проезда в поездах, причем экономика и условия проезда в поездах являются наиболее важными. Выводы исследования могут помочь коммерческим и общественным железнодорожным предприятиям в обеспечении необходимой инфраструктуры и условий для увеличения числа пассажиров.Ключевые слова: Экономика; Закон о пассажирах; Железнодорожные перевозки; Инфраструктура станции